2016
DOI: 10.1038/srep37428
|View full text |Cite
|
Sign up to set email alerts
|

Screening on binary Ti alloy with excellent mechanical property and castability for dental prosthesis application

Abstract: In the present study, the microstructure, mechanical property, castability, corrosion behavior and in vitro cytocompatibility of binary Ti–2X alloys with various alloying elements, including Ag, Bi, Ga, Ge, Hf, In, Mo, Nb, Sn and Zr, were systematically investigated, in order to assess their potential applications in dental field. The experimental results showed that all binary Ti‒2X alloys consisted entirely α–Ti phase. The tensile strength and microhardness of Ti were improved by adding alloying elements. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 39 publications
1
12
0
Order By: Relevance
“…The mechanical properties of Ti alloys are also influenced by adding Cr content because alloying improves the properties depending on their microstructures and phase compositions 29,30) . Both the yield and tensile strengths of the Ti-Cr specimens were approximately twice as high as those of the cp-Ti specimens.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanical properties of Ti alloys are also influenced by adding Cr content because alloying improves the properties depending on their microstructures and phase compositions 29,30) . Both the yield and tensile strengths of the Ti-Cr specimens were approximately twice as high as those of the cp-Ti specimens.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that this influences castability positively. Considering the results of the present study, it is concluded that increased Mo ratios improve the castability of Ti. The obtained results are similar to those in the literature, whereby the castability of Ti–Mo alloys has been improved by increased Mo content. 11 …”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
“…The obtained results are similar to those in the literature, whereby the castability of Ti–Mo alloys has been improved by increased Mo content. 11…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 2 more Smart Citations